Si Miss Packaging Tape At Ang Mundo Ng Ladies And Gentlemen - Espedido, Klara Domagtoy (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
This personal essay tackles the life of a transgender woman, the secret that was shared with her by her mami-mamihan, and the freedom that was brought by that secret. The narrative also highlights the complex yet indispensable and vibrant life of pageanteras behind the limelight—in every corner of a special place called backstage. It aims to emphasize that ramping up on stage to radiate happiness goes way beyond beauty and sparkle. Keywords Above all, I dedicate this essay to everyone who was crowned and will be crowned as Miss Packaging Tape. This is a celebration, a salute, and an act of dignifying the pedestal that has long been a witness to thousands of hidden and secluded narratives. Welcome to the world of Ladies and Gentlemen!